Controlling Metallurgical Phase Separation Reactions of the Ge0.87Pb0.13Te Alloy for High Thermoelectric Performance. Issue 6 (20th March 2013) - Gelbstein, Yaniv; Davidow, Joseph; Girard, Steven N.; Chung, Duck Young; Kanatzidis, Mercouri
Abstract We demonstrate the potential of metallurgical controlling of the phase separation reaction, by means of spark plasma sintering consolidation and subsequently controlled heat treatments sequence, for enhancement the thermoelectric properties of the p‐type Ge0.87Pb0.13Te composition. Very high ZTs of up to ∼2, attributed to the nucleation of sub‐micron phase separation domains and to comparable sized twinning and dislocation networks features, were observed. Based on the experimentally measured transport properties, combined with the previously reported phase separated n‐type (Pb0.95Sn0.05Te)0.92(PbS)0.08 composition, a maximal efficiency value of ∼11.5% was theoretically calculated. These ZT and efficiency values are among the highest reported for single composition non‐segmented bulk material legs.